The Medusa protocol - Hart, Rob (Fiction writer) (Hart, Rob (Fiction writer). Assassins Anonymous novel., 2025)
"Mark's protege Astrid has been kidnapped and is being held in a mysterious prison on a remote island off the coast of Brazil. Can she escape while keeping her pledge to not to take another life? When Astrid, known in her elite assassin days as Azrael, stopped showing up to Assassins Anonymous, the group assumed her past had caught up with her. Only Mark, Astrid's sponsor and formerly the deadliest assassin in the world, holds out hope that she's okay. Then the group gets a sign, or rather, a pizza delivery. Is there another psychopath out there who actually likes olives on their pizza, or is Astrid trying to send them a message? Meanwhile, Astrid woke up in a cell in a black site prison, on an island off the coast of Brazil. She has no idea why she's there. A doctor subjects her to mysterious experiments, plumbing the depths of her memory and looking for a vital clue from her past. Astrid will do anything to escape, oh, except...killing anyone. Damn. It's not so easy to blow this joint without actually blowing anything up."--